The Impact of Authentic Leadership, Teacher Competence, and Employee Competence on Student Satisfaction with Educational Services at the Madrasah Aliyah Negeri in the Semarang Residency - Handono, Handono; Nurochmah, Siti (Jurnal Pendidikan Islam, 2023)
Purpose – This research aims to determine the impact of the quality of authentic leadership, teacher competence, and employee competence, as well as their collective impact on satisfaction with educational services at MAN (Madrasah Aliyah Negeri) throughout the Semarang Residency. Design/methods/approach – The study employed a quantitative approach with a correlational method. The research population involved all stakeholders in the MAN of the Semarang Residency, with a total sample of 1021 respondents. Data were collected through questionnaires, and their validity was tested using validity and reliability tests. Data analysis was conducted using multiple linear regression analysis, preceded by classical assumption tests, including multicollinearity, heteroscedasticity, autocorrelation, and normality. Findings – The results significantly impact authentic leadership quality, teacher competence, and employee competence on satisfaction with educational services at MAN in the Semarang Residency. Additionally, authentic leadership, teacher competence, and employee competence collectively influence satisfaction with educational services at MAN in the Semarang Residency. Research implications – This research emphasizes the importance of authentic leadership, teacher competence, and employee competence in enhancing the satisfaction of educational services. These findings suggest the need for transparent leadership approaches and continuous professional development for teachers and support staff in educational environments.